A review on Ficus deltoidea medicinal properties and its potential use as ergogenic aids in athletes - Yaacob, Azhar; Baharuldin, Mohamad Taufik Hidayat (Universiti Putra Malaysia Press, 2018)
Ergogenic aids usage by athletes is a common scenario that can be seen in any level of athletes and any types of sports nowadays. Ergogenic aids can range from drugs, food, hormone, mechanical aid and herbs. Traditionally, ergogenic aids can be classified into categories namely: physiological, psychological, mechanical, pharmacological and nutrition. Despite all these classification, all ergogenic aids had one common purpose, which is to improve physical performance. Herbs consumption as ergogenic aids had been practiced since years ago by athletes as either nutritional or pharmacological aids. Using herbs as physical performance booster has gained popularity since it was claimed safer and natural. One of local herb that gets attention as energy booster is Ficus deltoidea (Mas Cotek). Ficus deltoidea had been used traditionally to restore energy. Few studies had reveal that Ficus deltoidea had medicinal properties such anti-nociceptive, antioxidant, wound healing enhancer and blood glucose regulation properties. There is no direct study on Ficus deltoidea as energy booster or ergogenic aids, but this medicinal value might be beneficial to increase athlete’s physical performance. Ergogenic aids, especially those that been produce using herbs, rarely have scientific evidence to determine its effectiveness, safety, dosage and mechanism of action. Ergogenic aids were normally marketed with claims and report as their reference, not scientific evidence. The most frequent claim used by traders is that ergogenic aids can increase and sustain body’s energy. This review will discuss on how ergogenic aids might help athletes to increase their physical performance and possibility of using Ficus deltoidea as ergogenic aids based on its medicinal properties.